2011
DOI: 10.1186/1475-2875-10-372
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of malaria microscopy and rapid diagnostic tests versus presumptive diagnosis: implications for malaria control in Uganda

Abstract: BackgroundCurrent Uganda National Malaria treatment guidelines recommend parasitological confirmation either by microscopy or rapid diagnostic test (RDT) before treatment with artemether-lumefantrine (AL). However, the cost-effectiveness of these strategies has not been assessed at rural operational primary care centres.MethodsThree health centres (HCs) were randomized to three diagnostic arms (microscopy, RDT and presumptive diagnosis) in a district of low and another of high malaria transmission intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 21 publications
(44 reference statements)
2
70
0
Order By: Relevance
“…Ideally, diagnostic testing for malaria, which has been previously shown to be cost-effective in Uganda and elsewhere in sub-Saharan Africa, will result in less presumptive therapy. 35,36 Regardless of government interventions, the majority of caregivers incurred costs to care for their febrile child. Although total expenditures were greater among households belonging to higher wealth quintiles, expenditures relative to household income (which was not assessed in this study) were likely higher among households in lower wealth quintiles.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, diagnostic testing for malaria, which has been previously shown to be cost-effective in Uganda and elsewhere in sub-Saharan Africa, will result in less presumptive therapy. 35,36 Regardless of government interventions, the majority of caregivers incurred costs to care for their febrile child. Although total expenditures were greater among households belonging to higher wealth quintiles, expenditures relative to household income (which was not assessed in this study) were likely higher among households in lower wealth quintiles.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in high transmission areas, some studies have found RDTs to be cost-effective compared with microscopy and presumptive treatment of malaria. 24 However, among children 5 years of age in high transmission settings, some investigators suggest that presumptive treatment of malaria may be more cost effective than RDTs given the high prevalence of malaria in this age group. 25 Economic factors may be weighed alongside other potential benefits of RDT use in decision-making for given regions.…”
Section: Discussionmentioning
confidence: 99%
“…Its implementation has been reported to be cost effective (Batwala et al, 2011), cause significant reduction in referrals and in patient's length of hospital stay (Boyce et al, 2015). Rapid diagnostic test is a device that detects malaria antigen in a small amount of blood, usually 5-15 µL, by immunochromatographic assay with monoclonal antibodies directed against the target parasite antigen and impregnated on a test strip (Wongsrichanalai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%